Essential amino acid index of sow’s colostrum - Michal Rolinec; Daniel Biró; Branislav Gálik; Milan Šimko; Miroslav Juráček; Ondrej Hanušovský (Journal of Central European Agriculture, 2018)
The aim of this study was to determine the protein quality of sow’s colostrum. For this purpose, the essential amino acid index (EAAI) of sow’s colostrum was calculated. The study was carried out on 12 Large white sows, which were on the 2.9 farrowing on average. Colostrum samples were collected by milking per hand without application of oxytocin. First sample were milked at time of birth of first piglet, and then every hour till 12th hour. Essential amino acids were determined using Amino Acid Analyser AAA400 (Ingos, Prague). For calculation of EAAI, the egg protein (EAAIegg) and protein of sow’s milk (EAAIsow’s milk) were used as standard. The highest value of EAAI was calculated for both at 4th h, EAAIegg 97.1%, EAAIsow’s milk 120.2%. The lowest values of EAAI were calculated at 12th h EAAIegg 78.3% and EAAIsow’s milk 96.9%. During the first 12 hours, protein of sow’s colostrum had not reached the quality of egg protein. Except sample collected at 12th hour after birth of first piglet, all colostrum samples had better quality of protein in comparison to sow’s milk. No significant (P>0.05) differences of EAAI between colostrum samples collected at different times from the birth of the first piglet till 12th h were observed.